Estudo experimental para avaliação da resistência à compressão entre dois modelos de fixação da osteotomia em L do fêmur proximal - Urnauer, Luciano (2013)
Introduction: Coxa brevis is a deformity of the proximal femur caused by a decrease or absence of growth of the physis of the proximal femur, usually caused by avascular necrosis present condition in conditions such as developmental dysplasia of the hip, proximal femoral epiphysiolysis, septic arthritis or disease Legg-Calvé-Perthes disease. Several surgeries have been proposed to lower the greater trochanter and femoral neck lengthening reestablishing the anatomy. Objective: To compare the mechanical tests by polyurethane in bone models the compressive strength of two different assemblies of plates for fixing osteotomy "L" of the proximal femur. Material and Methods: We used anatomical models of the proximal femur polyurethane which underwent an osteotomy longitudinal and divided into two groups with one group fixed with 4.5 DCP plate 10 holes with four screws proximal and three distal screws and fixed with a group 4.5 DCP plate 6 holes with two proximal and two distal screws. The anatomical models were tested for flexo in mechanical universal testing machine and was evaluated relative stiffness and linear movement. Results: By comparing the two groups in flexo tests, the average value of the relative stiffness in group 1 set with the long plate was 386.17 x10-3 N / m. In the group with the smaller plate fixed average value of the relative stiffness was 261,89 x10-3 N / m. The average linear displacement observed for an applied force of 1000 N in group 1 was 2.53 x10-3. In group 2, the mean value of linear displacement was 3.49 x 10-3m. Conclusion: Based on the parameters measured in the tests flexo, stability obtained by fixing the first group with a plate of ten holes was significantly higher than that obtained by fixing the second group with six holes of the plate.